Analysis Of current market position of Bangladesh for the baby wipes product and possible branding (promotional) strategies for the Savlon Baby Wipes. (New Savlon Product Range) - Azad, Md. Mohaiminul (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.